Association of Certification Level and Assertiveness with Accuracy of Calls Among Ice Hockey Referees - Wilson, A.; Mock, S. (International Journal of Sports Science and Coaching, 2013)
We examined the association of certification level and assertiveness of thirty ice-hockey referees with accuracy of penalty calls from viewing video clips of on-ice game situations. On average, referees had eight years of experience (min = 1 year, max = 32 years). Neither certification level nor assertiveness was significantly associated with referee accuracy. However, certification level was moderated by assertiveness such that the more certified and assertive the referees were, the more likely they were to make correct penalty calls ( p = 62). In contrast, referees who were highly certified and had lower assertiveness had the lowest probability of making a correct penalty call ( p = .03). Results are discussed in terms of the somatic marker hypothesis.